Respuesta :

Answer: x = -3

Step-by-step explanation: Isolate the variable by dividing each side by factors that do not contain a variable.

I hope this helps you out. :)

Answer:

x=−3

Step-by-step explanation:

8x+11−3x=2x+2

Step 1: Simplify both sides of the equation.

8x+11−3x=2x+2

8x+11+−3x=2x+2

(8x+−3x)+(11)=2x+2(Combine Like Terms)

5x+11=2x+2

5x+11=2x+2

Step 2: Subtract 2x from both sides.

5x+11−2x=2x+2−2x

3x+11=2

Step 3: Subtract 11 from both sides.

3x+11−11=2−11

3x=−9

Step 4: Divide both sides by 3.

3x

3

=

−9

3

x=−3

ACCESS MORE